Social media and brand engagement in the age of the customer - Lasuin, Charlie Albert; Omar, Azizah; Ramayah, T. (2015)
Social media environment has tremendously changed the landscape of marketing communication.Thanks to the development of Internet that creates marketers’ opportunity to tap the potential customer–Generation C and build a meaningful brand engagement with them. This paper will highlights the special ongoing issues pertaining to the growth of social media, mobile social, brand engagement and Generation C as basing to create firms’ sustainable competitive advantage. Marketers need to understand the real behaviour of customers, especially Generation C in order to formulate marketing communication strategies that suits with their lifestyles.